Analysis Of Ability, Discipline, Communication On Organizational Performance Mediated By Resilient Leadership Of Online Drivers In Batam - Antony Sentoso; Adi Neka Fatyandri; Mitha Veronica (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
Work ability, work discipline and communication certainly have an interrelated relationship, by running it according to procedures and directions all work will be easily completed. Therefore, the purpose of this study is to determine the effect of work ability, work discipline, communication, on company performance mediated by resilient leadership. The method uses quantitative analysis with the help of SEM PLS data processing tools. Data collection using questionnaires to a total of 580 ojol drivers in Batam City. The research variables consist of work ability (X1), work discipline (X2), communication (X3), leadership (Y1), and organizational performance (Y2). The results concluded that hypotheses 2, 3, 5, 6, and 7 can be accepted while hypotheses 1 and 4 are not accepted in this study because they have statements that are not strong with the results of the coefficient of determination test for the dependent variable value of 0.750 (75%) and the mediating variable is 0.691 (69.1%) and data quality (Goodness of Fit) of 0.702.